USM CONTINUES DEVELOPING MOOCs USING OPEN LEARNING PLATFORM - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
PENANG, 5 May 2017 – Online Learning Courses, also known as 'Massive Open Online Learning Courses’ (MOOCs), is nothing new to Universiti Sains Malaysia (USM) as it has embarked on developing it since 2015, and until now the university has successfully developed six MOOCs within the last two years.